If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
-(6*x)-3 = -63 // + 63
63-(6*x)-3 = 0
63-6*x-3 = 0
60-6*x = 0 // - 60
-6*x = -60 // : -6
x = -60/(-6)
x = 10
x = 10
| -9+2t=5 | | -3a+1=-17 | | -10+7b=60 | | 2+4t=-38 | | 10+4k=14 | | -6-4n=-26 | | 4t-5=19 | | -3n+6=-9 | | -2m+9=29 | | 8+6k=-40 | | 4+5k=24 | | -4w+8=-16 | | 4-7a=-10 | | 4d+9=33 | | -7a-8=-8 | | 4b+10=34 | | 3k+10=46 | | -5k+6=-49 | | 3t+2=35 | | 5m+9=19 | | 4d+3=7 | | -5t+2=-8 | | -7t-7=-42 | | 2b-7=5 | | -7k-9=-9 | | 3+5b=-12 | | 4d+5=-35 | | 6n+10=-2 | | -7-6m=23 | | -7d-2=5 | | -6t+8=-46 | | 3(x^2-2)=6 |